A heavy rare earth-free 54m neodymium-iron-boron permanent magnet material and a preparation method thereof

CN122889537APending Publication Date: 2026-10-09GUANGXI BAOCI NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610472683.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0011]本发明旨在解决现有无重稀土钕铁硼磁体磁性能协同性不足、微观结构调控精度低、制备工艺复杂冗余,且高磁能积与高温稳定性难以兼顾的技术短板,彻底摆脱Dy、Tb等重稀土依赖,在无重稀土条件下稳定实现54M牌号磁能积与矫顽力的协同达标

Benefits of technology

[0030]1.无重稀土高性能协同

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a kind of 54M neodymium-iron-boron permanent magnet materials without heavy rare earth and a preparation method thereof, and belongs to the technical field of rare earth permanent magnet materials.The material is composed of PrNd, B, Co, Cu, Al, Ga, Nb, Zr, Ti, Si, C, and the balance is Fe.The mass ratio of Pr to Nd in the PrNd alloy is 1:3.The material is processed by vacuum melting, rapid solidification, hydrogen fragmentation, airflow milling, magnetic field orientation pressing and cold isostatic pressing, low-temperature sintering, two-stage aging and post-processing, and is protected by inert gas atmosphere throughout the process and controlled by low-oxygen closed loop.The technical problems of insufficient magnetic performance synergy, difficulty in balancing high magnetic energy product and high coercivity, and poor high-temperature stability of existing rare-earth-free neodymium-iron-boron magnets are solved, and the core performance of 54M grade is stably realized.The material is suitable for new energy vehicle drive motor, servo motor, aerospace and other high-temperature harsh application scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of rare earth permanent magnet materials technology, specifically relating to a heavy rare earth-free 54M neodymium iron boron permanent magnet material and its preparation method. Background Technology

[0002] Sintered neodymium iron boron (NdFeB) permanent magnets, currently the best-performing permanent magnets in commercial applications, have become indispensable core materials in high-end industrial and technological fields such as high-end consumer electronics, servo motors, aerospace, and extreme environment sensors, thanks to their core advantages of high energy product, high coercivity, and high energy density. Among them, 54M grade NdFeB magnets are the mainstream grade used in these high-end fields due to their combination of high energy product and suitability for medium- and high-temperature service. Their core performance requirements are remanence Br ≥ 14.5 kGs, maximum energy product (BH)max ≥ 54 MGOe, and intrinsic coercivity Hcj ≥ 14 kOe. At the same time, there are stringent requirements for the magnets' high-temperature stability, batch consistency, and long-term service reliability.

[0003] Traditional high-grade NdFeB magnets typically require the addition of heavy rare earth elements such as Dy and Tb to meet the requirements for coercivity and high-temperature stability. However, heavy rare earth elements are globally scarce strategic resources with limited reserves, high prices, and significant supply fluctuations. This not only significantly increases the manufacturing cost of magnets but also inevitably reduces the remanence and energy product of the magnets due to the dilution effect of heavy rare earth elements on the ferromagnetic phase, making it difficult to achieve a synergistic improvement in both energy product and coercivity. Therefore, developing high-grade NdFeB magnets without heavy rare earth elements, freeing them from dependence on strategic resources while simultaneously achieving high performance and low cost, has become a core research and development direction and key technological challenge for the global NdFeB industry.

[0004] Currently, the industry has conducted a number of related studies on the composition design, microstructure control and preparation process of heavy rare earth neodymium iron boron materials. For example, Chinese patent application CN121565610A discloses a heavy rare earth-free NdFeB magnet and its preparation method, which adopts a dual-alloy design to improve the uniformity of alloy element melting distribution and the mechanical properties of the magnet; Chinese patent application CN121331582A discloses a heavy rare earth-free high-performance sintered NdFeB magnet and its preparation method, which optimizes the grain boundary phase structure through multi-stage aging and controlled cooling processes, achieving improved coercivity in a heavy rare earth-free system; Chinese patent application CN121191875A discloses a heavy rare earth-free NdFeB magnet and its preparation method, which further broadens the coercivity control range of the heavy rare earth-free system through multi-stage tempering processes and full-process impurity control; Chinese patent application CN120319600A discloses a NdFeB magnet material, its preparation method and application, which achieves grain refinement through magnetic powder particle size control, optimizing the coercivity level of the heavy rare earth-free system.

[0005] However, the aforementioned existing technologies still have a series of common defects and technical bottlenecks, which cannot meet the application requirements of high-end fields for 54M grade heavy rare earth neodymium iron boron magnets, as follows:

[0006] First, the synergy of magnetic properties is insufficient, making it impossible to consistently meet the core performance requirements of the 54M grade. Existing technologies generally focus on improving coercivity in heavy rare earth-free systems. Most solutions can achieve intrinsic coercivity of over 17 kOe, but they generally suffer from sacrificing remanence and energy product to improve coercivity. The energy product often fails to consistently reach the core threshold of ≥54 MGOe required for the 54M grade, making it difficult to simultaneously meet the synergistic requirements of high energy product and high coercivity. This makes it unsuitable for the stringent high energy density requirements of high-end fields.

[0007] Second, the precision of microstructure control is insufficient, making it impossible to explore the limits of magnetic properties in heavy rare earth-free systems. Existing technologies lack the ability to quantitatively control the microstructure of magnets. Although some schemes have achieved a certain degree of grain refinement, the main phase grain size after sintering is generally larger than 3.5 μm, and cannot be stably controlled within the ultra-fine and uniform range of 2~3 μm. At the same time, the thickness and continuity of the grain boundary phase have not been precisely quantitatively designed, making it impossible to achieve complete wetting of the grain boundary relative to the main phase grain at an ultra-thin grain boundary scale of 1~2 nm. This makes it difficult to eliminate the exchange coupling effect between grains, which greatly limits the further improvement of coercivity and magnetic energy product in heavy rare earth-free systems.

[0008] Third, the processes are highly complex, and their industrial adaptability and cost advantages are insufficient. To achieve performance optimization, existing technologies often employ complex processes such as three-stage or higher multi-level aging, dual-alloy methods, and grain boundary diffusion. These processes not only significantly extend the production cycle and increase preparation and testing costs, but also suffer from narrow process windows and difficulties in controlling batch stability of magnet performance, making it difficult to meet the dual demands of high performance and large-scale industrial production.

[0009] Fourth, high magnetic energy product and high-temperature stability are difficult to reconcile. Some existing technologies have limitations in their methods of limiting the Pr / Nd main rare earth ratio, making it difficult to balance the core contradiction between enhancing the magnetocrystalline anisotropy field of the main phase and maintaining remanence. This easily leads to fluctuations in magnetic properties due to unreasonable component ratios. Although some existing technologies can achieve high operating temperatures, this often comes at the cost of sacrificing magnetic energy product. It is difficult to achieve a stable 54M-level high magnetic energy product while simultaneously ensuring coercivity retention at 120℃, failing to meet the requirements of high-end applications that balance high energy density with mid-to-high temperature stability.

[0010] To address the aforementioned deficiencies in existing technologies, the present invention aims to provide a heavy rare earth-free 54M NdFeB permanent magnet material and its preparation method. Through precise multi-element synergistic composition ratio, dual-dimensional microstructure quantitative control, full-process low-oxygen closed-loop management, and a simple and efficient low-temperature sintering two-stage aging process, the core performance indicators of the 54M grade are stably achieved while completely removing heavy rare earth elements. This material balances high magnetic performance, high service reliability, low manufacturing cost, and excellent industrial adaptability, fully meeting the application needs of high-end consumer electronics, servo motors, aerospace, extreme environment sensors, and other high-end fields. Summary of the Invention

[0011] This invention aims to address the shortcomings of existing heavy rare earth-free NdFeB magnets, such as insufficient synergy of magnetic properties, low precision in microstructure control, complex and redundant preparation processes, and the difficulty in simultaneously achieving high energy product and high-temperature stability. It completely eliminates dependence on heavy rare earth elements like Dy and Tb, achieving stable synergy of energy product and coercivity for 54M grade magnets under heavy rare earth-free conditions. This invention provides a heavy rare earth-free 54M NdFeB permanent magnet material and its preparation method. Through precise multi-element proportioning, dual-dimensional quantitative control of grain and grain boundary, full-process low-oxygen management, and a low-temperature sintering two-stage aging process, it stably achieves 54M core magnetic properties and adaptability for high-temperature service at 120℃, balancing industrial mass production with low cost advantages, and meeting the stringent application requirements of high-end fields.

[0012] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0013] A heavy rare earth-free 54M neodymium iron boron permanent magnet material, comprising the following raw materials by mass percentage: PrNd 28~32%, B 0.98~1.08%, Co 1.0~2.0%, Cu 0.15~0.35%, Al 0.2~0.5%, Ga 0.08~0.2%, Nb 0.1~0.25%, Zr 0.08~0.2%, Ti 0.05~0.15%, Si 0.1~0.3%, C 0.02~0.05%, with the balance being Fe.

[0014] Furthermore, the mass ratio of Pr to Nd in the PrNd is 1:3.

[0015] Furthermore, the purity of PrNd is ≥99.5%, the purity of Fe is ≥99.9%, B is added in the form of ferroborone alloy, and the mass fraction of B in the ferroborone alloy is 20%. Co, Cu, Al, Ga, Nb, Zr, Ti, Si and C are all added in the form of high-purity elements, and the purity of the elements is ≥99.95%.

[0016] This invention also provides a method for preparing heavy rare earth-free 54M NdFeB permanent magnet material, comprising the following steps:

[0017] S1. Batching and Vacuum Melting: Weigh the raw materials according to the formula, place them in a vacuum induction melting furnace, and evacuate to a vacuum level of ≤5×10⁻⁶. - 3 Pa, filled with high-purity argon gas for protection, melted and held at 1450~1550℃ for 15~30min to obtain a uniform alloy melt;

[0018] S2. Preparation of rapidly solidified alloy sheets: The alloy melt is transferred to the heat preservation bag of the rapidly solidified alloy sheet casting machine, and the melt temperature is controlled at 1400~1480℃. Under the protection of high-purity argon gas, the alloy melt is sprayed onto a high-speed rotating copper roller for casting. The roller speed is 1.2~2.0m / s, and rapidly solidified alloy sheets are prepared.

[0019] S3. Hydrogen-crushing treatment: Place the rapidly solidified alloy sheet into a hydrogen-crushing furnace, seal it, and then evacuate it to ≤1×10⁻⁶. -2 Pa, purge with high-purity hydrogen until the hydrogen pressure inside the furnace is 0.1~0.3 MPa, and absorb hydrogen at room temperature for 2~4 hours; then evacuate to ≤1×10 -3 Pa, heat to 500~600℃ and hold for 3~5h to remove hydrogen, and after cooling, obtain 30~80 mesh hydrogen fragment powder;

[0020] S4. Ultrafine grinding by air jet milling: Hydrogen-crushed powder is fed into an air jet mill, using high-purity nitrogen as the grinding medium. The grinding pressure is controlled at 0.6~1.0 MPa and the classifier speed at 3500~5000 rpm to obtain a median particle size D. 50 Magnetic powder with a particle size of 2.0~3.5μm;

[0021] S5. Magnetic field orientation pressing and cold isostatic pressing: Magnetic powder is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The forming pressure is controlled at 10~20MPa and the holding time is 5~20s to obtain an orientation compact; after vacuum sealing, the compact is cold isostatically pressed at a pressure of 150~250MPa for 10~30s.

[0022] S6. Low-temperature sintering and two-stage aging treatment: The compact is fed into a high-vacuum sintering furnace, with high-purity argon gas protection throughout the process, and the vacuum degree inside the furnace is ≤5×10⁻⁶. -3 Pa, first heat to 1020~1040℃ and hold for 2~4h to complete sintering, then quench with argon gas to room temperature; then heat to 830~870℃ and hold for 1~3h, then quench with argon gas to room temperature; finally heat to 470~510℃ and hold for 2~4h, then quench with argon gas to room temperature to obtain sintered magnet.

[0023] S7. Post-processing: The sintered magnets are mechanically processed as required to obtain the finished product of heavy rare earth-free 54M neodymium iron boron permanent magnet material.

[0024] Furthermore, in step S2, under the protective atmosphere of high-purity argon, the vacuum level inside the furnace is controlled to be ≤1×10⁻⁶. -2Pa.

[0025] Furthermore, in step S2, the thickness of the rapidly solidified alloy sheet is 0.2~0.4 mm, and the mass percentage of the α-Fe phase is ≤5%.

[0026] Furthermore, in step S4, the purity of the high-purity nitrogen gas is ≥99.999% and the oxygen content is ≤5ppm.

[0027] Furthermore, in step S4, the air jet milling process for ultrafine powdering is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is controlled to be ≤300ppm.

[0028] Further, in step S6, the temperature is first increased to 1020-1040℃ at a rate of 3-8℃ / min; then increased to 830-870℃ at a rate of 5-10℃ / min; and finally increased to 470-510℃ at a rate of 5-10℃ / min.

[0029] Compared with the prior art, the technical advantages of the present invention are as follows:

[0030] 1. High-performance synergy without heavy rare earth elements

[0031] This invention, through precise multi-element synergistic composition design, achieves stable core performance indicators for the 54M grade while completely removing heavy rare earth elements such as Dy and Tb: a maximum magnetic energy product (BH)max of 54.16~54.95 MGOe, intrinsic coercivity Hcj of 14.23~15.24 kOe, remanence Br of 14.53~14.82 kGs, and a demagnetization curve squareness Hk / Hcj > 93%, thus eliminating dependence on scarce strategic resources. Unlike existing technologies where high coercivity inevitably sacrifices magnetic energy product, this invention, through the precise Pr / Nd ratio of 1:3 and the synergistic effect of the Nb-Zr-Ti ternary grain refinement system and the Cu-Al-Ga grain boundary control system, significantly improves coercivity while ensuring high saturation magnetization of the main phase. This solves the industry problem of achieving high magnetic energy product and high coercivity synergistically in systems without heavy rare earth elements, providing a high-performance and low-cost solution for high-end applications.

[0032] 2. Precise regulation of dual-dimensional microstructure

[0033] This invention establishes a dual-dimensional quantitative control mechanism for grain and grain boundary, stably controlling the main phase grain size within an ultrafine and uniform range of 2.14~2.97μm, significantly superior to the conventional grain size levels of existing technologies in the industry. The grain boundary phase thickness is controlled in an ultrathin and continuous state of 1.24~1.82nm, wetting the surface of the main phase grains. By precipitating a nanoscale second phase at the grain boundaries using Nb-Zr-Ti to pin grain boundary migration, combined with the synergistic effect of Cu-Al-Ga lowering the melting point of the grain boundary phase and optimizing wettability, the entire grain growth process is suppressed, and the grain boundary structure is precisely constructed. This dual-dimensional control mechanism effectively eliminates the exchange coupling effect between grains, significantly improving coercivity while minimizing the loss of relative remanence at grain boundaries, breaking through the magnetic performance limit of heavy rare earth-free systems. The squareness of the demagnetization curve reaches over 93%, demonstrating excellent dynamic anti-demagnetization capability.

[0034] 3. Low-temperature, short-time, high-efficiency sintering process

[0035] This invention employs a low-temperature sintering process of 1020~1040℃, with a holding time of only 2~4 hours. The sintering temperature is lower than the conventional sintering range of 1040~1070℃, while the holding time is significantly reduced, effectively shortening the sintering cycle. This process relies on the grain boundary pinning effect of high-melting-point Nb-Zr-Ti elements, combined with a compositional design that synergistically regulates the melting point of the grain boundary phase using Co-Ga. This effectively suppresses abnormal growth of the main phase grains while ensuring sufficient densification of the magnet, achieving a density of over 99.5%. Coupled with a matching 830~870℃ / 470~510℃ two-stage aging process, it achieves gradient reconstruction and structural stabilization of the grain boundary phase, avoiding the complex and lengthy process of three or more multi-stage aging. This simple and efficient process has a wide process window, high control tolerance, and caters to both high performance and large-scale mass production requirements, making it highly adaptable to industrial applications.

[0036] 4. Closed-loop management of hypoxia throughout the entire process

[0037] This invention establishes a closed-loop low-oxygen control system from raw materials to finished products: During the rapid solidification and spinning stage, the α-Fe phase is controlled to ≤5% to ensure microstructure uniformity; high-purity nitrogen is used for grinding during the air jet milling stage, resulting in an oxygen content of ≤300ppm in the magnetic powder; and after sintering, the oxygen content of the magnet is ≤440ppm. Through inert atmosphere protection, quantitative limitation of oxygen content at key nodes, and vacuum sealing, the oxidation of the main phase grains and the formation of impurity phases are effectively suppressed, ensuring the purity and continuity of the grain boundary phase. This control system enables the magnet to achieve a high density of over 99.5% even under low-temperature sintering conditions, avoiding magnetic performance degradation and batch fluctuations caused by oxidation. It provides key process support for the high-performance stability of heavy rare earth-free systems and solves the performance dispersion problem caused by the crude oxygen control in existing technologies.

[0038] 5. Breakthrough in reliability during high-temperature service

[0039] This invention precisely adds Co to raise the Curie temperature of the main phase to over 332℃, and combines this with Ga to optimize the high-temperature stability of the grain boundary phase, achieving a coercivity retention rate of ≥71% and up to 79.91% at 120℃. This far exceeds the 100℃ standard operating temperature requirement for 54M grade magnets, ensuring stable operation in 120℃ high-temperature environments. Unlike existing technologies that sacrifice magnetic energy product for high-temperature performance or suffer from insufficient high-temperature retention, this invention simultaneously guarantees excellent high-temperature stability while stably achieving a 54M-level high magnetic energy product, solving the industry pain point of balancing high magnetic energy product and high-temperature service reliability in heavy rare-earth-free NdFeB magnets. This characteristic enables the magnets to have long-term service reliability in harsh high-temperature environments such as new energy vehicle drive motors and aerospace, expanding the application boundaries of heavy rare-earth-free high-performance magnets. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. The following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of this invention.

[0041] A heavy rare earth-free 54M neodymium iron boron permanent magnet material, comprising the following raw materials by mass percentage:

[0042] The alloy composition is as follows: PrNd 28~32%, B 0.98~1.08%, Co 1.0~2.0%, Cu 0.15~0.35%, Al 0.2~0.5%, Ga 0.08~0.2%, Nb 0.1~0.25%, Zr 0.08~0.2%, Ti 0.05~0.15%, Si 0.1~0.3%, C 0.02~0.05%, with the balance being Fe. In the PrNd alloy, the mass ratio of Pr to Nd is 1:3, the alloy purity is ≥99.5%, the Fe purity is ≥99.9%, and B is added in the form of a B-Fe alloy (the mass fraction of B in the B-Fe alloy is 20%). Co, Cu, Al, Ga, Nb, Zr, Ti, Si, and C are all added in high-purity elemental form with an elemental purity ≥99.95%.

[0043] A method for preparing a heavy rare-earth-free 54M NdFeB permanent magnet material includes the following steps:

[0044] S1. Batching and Vacuum Melting: Weigh each raw material according to the above mass percentage formula, place the weighed raw materials into a vacuum induction melting furnace, and evacuate the furnace until the vacuum degree inside the furnace is ≤5×10. -3 Pa is filled with high-purity argon as a protective atmosphere, and smelting is carried out at 1450~1550℃ for 15~30 minutes to completely melt the raw materials and make the composition uniform, thus obtaining an alloy melt.

[0045] S2. Rapid Solidification and Strip Spinning Preparation: The alloy melt obtained in step S1 is transferred to the holding bath of the rapid solidification and strip spinning machine. The melt temperature is controlled at 1400~1480℃ under a high-purity argon protective atmosphere (furnace vacuum degree ≤1×10⁻⁶). -2 The alloy melt is sprayed onto a high-speed rotating copper roller for spinning. The roller speed is controlled at 1.2~2.0m / s to prepare a rapidly solidified alloy sheet with a thickness of 0.2~0.4mm. The rapidly solidified sheet has no coarse α-Fe precipitates and the mass percentage of α-Fe phase is ≤5%.

[0046] S3. Hydrogen Crushing Treatment: Place the rapidly solidified alloy sheet obtained in step S2 into a hydrogen crushing furnace, seal it, and then evacuate the furnace until the vacuum level is ≤1×10⁻⁶. -2 The furnace is filled with high-purity hydrogen gas (≥99.999%) to a pressure of 0.1~0.3 MPa, and hydrogen absorption is performed at room temperature for 2~4 hours to ensure complete hydrogenation and breakage of the alloy. Subsequently, the hydrogenated alloy undergoes dehydrogenation treatment, and the furnace is evacuated to a vacuum level ≤1×10⁻⁶. -3 Pa, heat to 500~600℃, hold for 3~5h, cool to room temperature after dehydrogenation to obtain hydrogen fragment powder, the particle size of the hydrogen fragment powder is controlled at 30~80 mesh.

[0047] S4. Ultrafine grinding by air jet milling: The hydrogen-rich powder obtained in step S3 is fed into an air jet mill. High-purity nitrogen gas with a purity ≥99.999% and an oxygen content ≤5ppm is used as the grinding medium. The grinding pressure is controlled at 0.6~1.0MPa, and the classifier speed is controlled at 3500~5000rpm for ultrafine grinding to prepare a median particle size D. 50 The magnetic powder is 2.0~3.5μm in size; the entire process is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is strictly controlled to be ≤300ppm.

[0048] S5. Magnetic field orientation pressing and cold isostatic pressing: The magnetic powder obtained in step S4 is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The pressing pressure is controlled at 10~20MPa and the holding time is 5~20s to obtain an orientation compact. The compact is immediately vacuum sealed and then subjected to cold isostatic pressing. The cold isostatic pressing pressure is controlled at 150~250MPa and the holding time is 10~30s.

[0049] S6. Low-temperature sintering and two-stage aging treatment: The pressed billet obtained in step S5 is fed into a high-vacuum sintering furnace, and the entire process is carried out under a high-purity argon protective atmosphere, controlling the vacuum degree inside the furnace to ≤5×10⁻⁶. -3Pa is subjected to low-temperature sintering and two-stage aging treatment in sequence: first, the temperature is raised to 1020~1040℃ at a heating rate of 3~8℃ / min and held for 2~4h to complete sintering, and then high-purity argon gas is introduced for gas quenching to room temperature; then, the temperature is raised to 830~870℃ at a heating rate of 5~10℃ / min and held for 1~3h before gas quenching to room temperature; finally, the temperature is raised to 470~510℃ at a heating rate of 5~10℃ / min and held for 2~4h before gas quenching to room temperature to obtain sintered magnets.

[0050] S7. Post-processing: The sintered magnet obtained in step S6 is mechanically processed according to application requirements to obtain the finished product of heavy rare earth-free 54M NdFeB permanent magnet material.

[0051] Technical principle of the invention:

[0052] 1. Functions and mechanisms of action of each component

[0053] PrNd alloy as Nd2Fe 14 The core forming elements of the B-type 2:14:1 hard magnetic main phase provide the fundamental magnetic moment and intrinsic magnetocrystalline anisotropy for the magnet. By fixing the mass ratio of Pr to Nd to 1:3, the reduction in remanence caused by excessive Pr is avoided, while maximizing the optimization of the magnetocrystalline anisotropy field of the main phase. This provides core support for the synergy of high remanence and high coercivity in heavy rare earth-free systems, ensuring the rare earth substrate required for grain boundary phase construction.

[0054] B is the component that forms Nd2Fe. 14 Essential elements for the B-type 2:14:1 hard magnetic main phase, participating in the construction of the main phase lattice, directly determining the formation ratio and structural integrity of the main phase, and are one of the core elements that ensure the basic hard magnetic properties of magnets.

[0055] Co can partially enter the main phase lattice through atomic substitution, effectively increasing the Curie temperature of the main phase and significantly improving the high-temperature thermal stability of the magnet. At the same time, it can form a synergistic effect with Ga, optimizing the melting point and wettability of rare earth-rich grain boundary phases, assisting in the precise control of grain boundary structure, and also mitigating the attenuation of magnetic properties of the magnet under high-temperature conditions to a certain extent.

[0056] The synergistic formation of Cu, Al, and Ga into a low-melting-point grain boundary control system can effectively reduce the melting temperature of rare-earth-rich grain boundary phases, broaden the sintering and aging process windows, significantly improve the wetting effect of grain boundaries on the main phase grains, promote the formation of continuous, uniform, and ultra-thin rare-earth-rich grain boundary phases, achieve magnetic isolation between main phase grains, eliminate the exchange coupling effect between grains, and minimize the loss of relative remanence of grain boundaries while greatly improving coercivity.

[0057] The three elements Nb, Zr, and Ti work together to form a high-melting-point grain refinement and grain boundary pinning system. During sintering, nanoscale second phases can preferentially precipitate at grain boundaries, firmly pinning grain boundary migration and effectively suppressing abnormal growth of main phase grains during high-temperature sintering. This enables fine control of grain size throughout the entire process, while also optimizing the structural stability of grain boundaries and further enhancing the coercivity improvement effect.

[0058] Si can suppress the precipitation of coarse α-Fe phase during melting and spinning, optimize the uniformity of the microstructure of rapidly solidified alloy sheets, purify the grain boundary phase, optimize the electrical conductivity of the grain boundary phase, which is beneficial to reduce eddy current loss of magnets in high-frequency applications, and can also help improve the uniformity of grain boundary phase distribution and enhance the batch stability of magnetic properties.

[0059] C can further refine grains during sintering, suppress excessive migration of grain boundaries and grain coarsening, fill the micropores formed during sintering, improve the density and mechanical strength of the magnet, suppress excessive flow of grain boundary phases, maintain the structural stability of ultrathin continuous grain boundaries, and reduce the impact of process fluctuations on magnetic properties.

[0060] Fe, as the core matrix element of the main phase, provides high saturation magnetization for the magnet and is the basic element to ensure high remanence and high energy product of the magnet. By adjusting the balance of the total components, the performance regulation needs of different scenarios can be met.

[0061] 2. Core preparation process principle and synergistic effect

[0062] In the melting and rapid solidification stage, vacuum high-temperature melting ensures the full dissolution and uniform distribution of each component, avoiding elemental segregation. Combined with appropriate melt temperature and copper roller speed, rapidly solidified flakes with uniform microstructure and α-Fe precipitation ≤5% are obtained, reducing coarse and abnormal microstructures from the source and laying the foundation for subsequent powdering and sintering grain refinement. The hydrogen crushing and air jet milling stages employ gentle hydrogen absorption and dehydrogenation with high-purity nitrogen grinding to obtain uniformly sized ultrafine magnetic powder without damaging the grain structure. Simultaneously, oxygen content is strictly controlled to prevent irreversible loss of magnetic properties due to powder oxidation, providing high-quality raw materials for magnetic field orientation and sintering densification.

[0063] The magnetic field forming and cold isostatic pressing processes enhance the orientation degree of the magnetic powder and the density of the green body through strong magnetic field orientation and high-pressure densification, reducing internal porosity and preventing abnormal grain growth caused by uneven stress during sintering, thus further ensuring the uniformity of the microstructure. Low-temperature sintering and two-stage aging are the core elements of the composition and process synergy of this invention. Low-temperature sintering, while ensuring densification, works in conjunction with the pinning effect of Nb, Zr, and Ti nanophases to stably control the grain size within the ultrafine range. The first-stage high-temperature aging promotes the uniform spreading and wetting of the grain boundary phases, while the second-stage low-temperature aging optimizes the composition and structure of the grain boundaries, ultimately forming continuous ultrathin grain boundaries and blocking the exchange coupling between grains.

[0064] In the entire system, the functions of alloying elements and process parameters are highly matched: the PrNd ratio determines the intrinsic magnetic properties, Co enhances high-temperature stability, Cu, Al, and Ga regulate grain boundary morphology, Nb, Zr, and Ti pin and refine grains, and Si and C suppress impurities and improve density; while processes such as vacuum melting, low-oxygen powder preparation, low-temperature sintering, and two-stage aging provide the conditions for the elements to function. The two support each other and work synergistically to achieve high magnetic energy product of 54M, high coercivity, and excellent high-temperature stability simultaneously under heavy rare earth conditions.

[0065] The present invention will be further illustrated below through specific embodiments and comparative examples.

[0066] Example 1

[0067] A heavy rare earth-free 54M neodymium iron boron permanent magnet material, comprising the following raw materials by mass percentage:

[0068] The alloy composition is as follows: PrNd 28%, B 0.98%, Co 1.0%, Cu 0.15%, Al 0.2%, Ga 0.08%, Nb 0.1%, Zr 0.08%, Ti 0.05%, Si 0.1%, C 0.02%, with the balance being Fe. The mass ratio of Pr to Nd in the PrNd alloy is 1:3, with an alloy purity ≥99.5% and Fe purity ≥99.9%. B is added in the form of a B-Fe alloy (B mass fraction in the B-Fe alloy is 20%). Co, Cu, Al, Ga, Nb, Zr, Ti, Si, and C are all added in high-purity elemental form with an elemental purity ≥99.95%.

[0069] A method for preparing a heavy rare-earth-free 54M NdFeB permanent magnet material includes the following steps:

[0070] S1. Batching and Vacuum Melting: Weigh each raw material according to the above-mentioned mass percentage formula, place the weighed raw materials into a vacuum induction melting furnace, and evacuate the furnace until the vacuum degree inside the furnace is ≤5×10. -3 Pa is filled with high-purity argon as a protective atmosphere, and smelting is carried out at 1450℃ for 30 minutes to completely melt the raw materials and obtain a uniform composition, thus obtaining an alloy melt.

[0071] S2. Rapid Solidification and Strip Spinning Preparation: The alloy melt obtained in step S1 is transferred to the heat preservation pot of the rapid solidification and strip spinning machine. The melt temperature is controlled at 1400℃ under a high-purity argon protective atmosphere (furnace vacuum degree ≤1×10⁻⁶). -2 The alloy melt is sprayed onto a high-speed rotating copper roller for spinning. The roller speed is controlled at 1.2 m / s to prepare a rapidly solidified alloy sheet with a thickness of 0.2~0.4 mm.

[0072] S3. Hydrogen Crushing Treatment: Place the rapidly solidified alloy sheet obtained in step S2 into a hydrogen crushing furnace, seal it, and then evacuate the furnace until the vacuum level is ≤1×10⁻⁶. -2 The furnace was filled with high-purity hydrogen gas (≥99.999%) until the internal hydrogen pressure reached 0.1 MPa. Hydrogen absorption was performed at room temperature for 4 hours to ensure complete hydrogenation and breakage of the alloy. Subsequently, the hydrogenated alloy underwent dehydrogenation treatment, and the furnace was evacuated to a vacuum level ≤1×10⁻⁶. -3 Pa, heat to 500℃, hold for 5 hours, and after dehydrogenation is completed, cool to room temperature and remove from the furnace to obtain hydrogen fragment powder. The particle size of the hydrogen fragment powder is controlled at 30~80 mesh.

[0073] S4. Ultrafine grinding by air jet milling: The hydrogen-rich powder obtained in step S3 is fed into an air jet mill. High-purity nitrogen gas with a purity ≥99.999% and an oxygen content ≤5ppm is used as the grinding medium. The grinding pressure is controlled at 0.6MPa and the classifier wheel speed is 3500rpm for ultrafine grinding to obtain a median particle size D. 50 The magnetic powder is 2.0~3.5μm in size; the entire process is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is strictly controlled to be ≤300ppm.

[0074] S5. Magnetic field orientation pressing and cold isostatic pressing: The magnetic powder obtained in step S4 is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The pressing pressure is controlled at 10MPa and the holding time is 20s to obtain an orientation compact. The compact is immediately vacuum sealed and then subjected to cold isostatic pressing. The cold isostatic pressing pressure is controlled at 150MPa and the holding time is 30s.

[0075] S6. Low-temperature sintering and two-stage aging treatment: The pressed billet obtained in step S5 is fed into a high-vacuum sintering furnace, and the entire process is carried out under a high-purity argon protective atmosphere, controlling the vacuum degree inside the furnace to ≤5×10⁻⁶. -3 Pa was subjected to low-temperature sintering and two-stage aging treatment in sequence: first, the temperature was raised to 1020℃ at a heating rate of 3℃ / min and held for 4 hours to complete sintering, and then high-purity argon gas was introduced for gas quenching to room temperature; then, the temperature was raised to 830℃ at a heating rate of 5℃ / min and held for 3 hours before being gas quenched to room temperature; finally, the temperature was raised to 470℃ at a heating rate of 5℃ / min and held for 4 hours before being gas quenched to room temperature to obtain the sintered magnet.

[0076] S7. Post-processing: The sintered magnet obtained in step S6 is mechanically processed according to application requirements to obtain the finished product of heavy rare earth-free 54M NdFeB permanent magnet material.

[0077] Example 2

[0078] A heavy rare earth-free 54M neodymium iron boron permanent magnet material, comprising the following raw materials by mass percentage:

[0079] The alloy composition is as follows: PrNd 29%, B 1.00%, Co 1.3%, Cu 0.20%, Al 0.28%, Ga 0.12%, Nb 0.14%, Zr 0.12%, Ti 0.08%, Si 0.15%, C 0.03%, with the balance being Fe. The mass ratio of Pr to Nd in the PrNd alloy is 1:3, with an alloy purity ≥99.5% and Fe purity ≥99.9%. B is added in the form of a B-Fe alloy (B mass fraction in the B-Fe alloy is 20%). Co, Cu, Al, Ga, Nb, Zr, Ti, Si, and C are all added in high-purity elemental form with an elemental purity ≥99.95%.

[0080] A method for preparing a heavy rare-earth-free 54M NdFeB permanent magnet material includes the following steps:

[0081] S1. Batching and Vacuum Melting: Weigh each raw material according to the above-mentioned mass percentage formula, place the weighed raw materials into a vacuum induction melting furnace, and evacuate the furnace until the vacuum degree inside the furnace is ≤5×10. -3 Pa is filled with high-purity argon as a protective atmosphere, and smelting is carried out at 1470℃ for 25 minutes to completely melt the raw materials and obtain a uniform composition, thus obtaining an alloy melt.

[0082] S2. Rapid Solidification and Strip Spinning Preparation: The alloy melt obtained in step S1 is transferred to the heat preservation pot of the rapid solidification and strip spinning machine. The melt temperature is controlled at 1420℃ under a high-purity argon protective atmosphere (furnace vacuum degree ≤1×10⁻⁶). -2 The alloy melt is sprayed onto a high-speed rotating copper roller for spinning. The roller speed is controlled at 1.4 m / s to prepare a rapidly solidified alloy sheet with a thickness of 0.2~0.4 mm.

[0083] S3. Hydrogen Crushing Treatment: Place the rapidly solidified alloy sheet obtained in step S2 into a hydrogen crushing furnace, seal it, and then evacuate the furnace until the vacuum level is ≤1×10⁻⁶. -2 The furnace was filled with high-purity hydrogen gas (≥99.999%) until the internal hydrogen pressure reached 0.15 MPa. Hydrogen absorption was performed at room temperature for 3.5 hours to ensure complete hydrogenation and breakage of the alloy. Subsequently, the hydrogenated alloy underwent dehydrogenation treatment, and the furnace was evacuated to a vacuum level ≤1×10⁻⁶. -3 Pa, heat to 520℃, hold for 4.5h, and after dehydrogenation is completed, cool to room temperature and remove from the furnace to obtain hydrogen fragment powder. The particle size of the hydrogen fragment powder is controlled at 30~80 mesh.

[0084] S4. Ultrafine grinding by air jet milling: The hydrogen-rich powder obtained in step S3 is fed into an air jet mill. High-purity nitrogen gas with a purity ≥99.999% and an oxygen content ≤5ppm is used as the grinding medium. The grinding pressure is controlled at 0.7MPa and the classifier wheel speed is 3800rpm for ultrafine grinding to obtain a median particle size D. 50The magnetic powder is 2.0~3.5μm in size; the entire process is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is strictly controlled to be ≤300ppm.

[0085] S5. Magnetic field orientation pressing and cold isostatic pressing: The magnetic powder obtained in step S4 is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The pressing pressure is controlled at 13MPa and the holding time is 15s to obtain an orientation compact. The compact is immediately vacuum sealed and then subjected to cold isostatic pressing. The cold isostatic pressing pressure is controlled at 180MPa and the holding time is 25s.

[0086] S6. Low-temperature sintering and two-stage aging treatment: The pressed billet obtained in step S5 is fed into a high-vacuum sintering furnace, and the entire process is carried out under a high-purity argon protective atmosphere, controlling the vacuum degree inside the furnace to ≤5×10⁻⁶. -3 Pa was subjected to low-temperature sintering and two-stage aging treatment in sequence: first, the temperature was increased to 1025℃ at a heating rate of 4℃ / min and held for 3.5h to complete sintering, followed by gas quenching with high-purity argon to room temperature; then, the temperature was increased to 840℃ at a heating rate of 6℃ / min and held for 2.5h before gas quenching to room temperature; finally, the temperature was increased to 480℃ at a heating rate of 6℃ / min and held for 3.5h before gas quenching to room temperature to obtain the sintered magnet.

[0087] S7. Post-processing: The sintered magnet obtained in step S6 is mechanically processed according to application requirements to obtain the finished product of heavy rare earth-free 54M NdFeB permanent magnet material.

[0088] Example 3

[0089] A heavy rare earth-free 54M neodymium iron boron permanent magnet material, comprising the following raw materials by mass percentage:

[0090] The alloy composition is as follows: PrNd 30%, B 1.03%, Co 1.5%, Cu 0.25%, Al 0.35%, Ga 0.15%, Nb 0.18%, Zr 0.15%, Ti 0.10%, Si 0.2%, C 0.03%, with the balance being Fe. The mass ratio of Pr to Nd in the PrNd alloy is 1:3, with an alloy purity ≥99.5% and Fe purity ≥99.9%. B is added in the form of a B-Fe alloy (B mass fraction in the B-Fe alloy is 20%). Co, Cu, Al, Ga, Nb, Zr, Ti, Si, and C are all added in high-purity elemental form with an elemental purity ≥99.95%.

[0091] A method for preparing a heavy rare-earth-free 54M NdFeB permanent magnet material includes the following steps:

[0092] S1. Batching and Vacuum Melting: Weigh each raw material according to the above-mentioned mass percentage formula, place the weighed raw materials into a vacuum induction melting furnace, and evacuate the furnace until the vacuum degree inside the furnace is ≤5×10. -3 Pa is filled with high-purity argon as a protective atmosphere, and smelting is carried out at 1500℃ for 20 minutes to completely melt the raw materials and make the composition uniform, thus obtaining an alloy melt.

[0093] S2. Rapid Solidification and Strip Spinning Preparation: The alloy melt obtained in step S1 is transferred to the heat preservation pot of the rapid solidification and strip spinning machine. The melt temperature is controlled at 1450℃ under a high-purity argon protective atmosphere (furnace vacuum degree ≤1×10⁻⁶). -2 The alloy melt is sprayed onto a high-speed rotating copper roller for spinning. The roller speed is controlled at 1.5 m / s to prepare a rapidly solidified alloy sheet with a thickness of 0.2~0.4 mm.

[0094] S3. Hydrogen Crushing Treatment: Place the rapidly solidified alloy sheet obtained in step S2 into a hydrogen crushing furnace, seal it, and then evacuate the furnace until the vacuum level is ≤1×10⁻⁶. -2 The furnace was filled with high-purity hydrogen gas (≥99.999%) until the internal hydrogen pressure reached 0.2 MPa. Hydrogen absorption was performed at room temperature for 3 hours to ensure complete hydrogenation and breakage of the alloy. Subsequently, the hydrogenated alloy underwent dehydrogenation treatment, and the furnace was evacuated to a vacuum level ≤1×10⁻⁶. -3 Pa, heat to 550℃, hold for 4 hours, and after dehydrogenation is completed, cool to room temperature and remove from the furnace to obtain hydrogen fragment powder. The particle size of the hydrogen fragment powder is controlled at 30~80 mesh.

[0095] S4. Ultrafine grinding by air jet milling: The hydrogen-rich powder obtained in step S3 is fed into an air jet mill. High-purity nitrogen gas with a purity ≥99.999% and an oxygen content ≤5ppm is used as the grinding medium. The grinding pressure is controlled at 0.8MPa and the classifier wheel speed is 4200rpm for ultrafine grinding to obtain a median particle size D. 50 The magnetic powder is 2.0~3.5μm in size; the entire process is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is strictly controlled to be ≤300ppm.

[0096] S5. Magnetic field orientation pressing and cold isostatic pressing: The magnetic powder obtained in step S4 is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The pressing pressure is controlled at 15MPa and the holding time is 15s to obtain an orientation compact. The compact is immediately vacuum sealed and then subjected to cold isostatic pressing. The cold isostatic pressing pressure is controlled at 200MPa and the holding time is 20s.

[0097] S6. Low-temperature sintering and two-stage aging treatment: The pressed billet obtained in step S5 is fed into a high-vacuum sintering furnace, and the entire process is carried out under a high-purity argon protective atmosphere, controlling the vacuum degree inside the furnace to ≤5×10⁻⁶. -3Pa was subjected to low-temperature sintering and two-stage aging treatment in sequence: first, the temperature was raised to 1030℃ at a heating rate of 6℃ / min and held for 3 hours to complete sintering, and then high-purity argon gas was introduced for gas quenching to room temperature; then, the temperature was raised to 850℃ at a heating rate of 8℃ / min and held for 2 hours before being gas quenched to room temperature; finally, the temperature was raised to 490℃ at a heating rate of 8℃ / min and held for 3 hours before being gas quenched to room temperature to obtain the sintered magnet.

[0098] S7. Post-processing: The sintered magnet obtained in step S6 is mechanically processed according to application requirements to obtain the finished product of heavy rare earth-free 54M NdFeB permanent magnet material.

[0099] Example 4

[0100] A heavy rare earth-free 54M neodymium iron boron permanent magnet material, comprising the following raw materials by mass percentage:

[0101] The alloy composition is as follows: PrNd 31%, B 1.05%, Co 1.8%, Cu 0.30%, Al 0.42%, Ga 0.18%, Nb 0.22%, Zr 0.18%, Ti 0.12%, Si 0.25%, C 0.04%, with the balance being Fe. The mass ratio of Pr to Nd in the PrNd alloy is 1:3, with an alloy purity ≥99.5% and Fe purity ≥99.9%. B is added in the form of a B-Fe alloy (B mass fraction in the B-Fe alloy is 20%). Co, Cu, Al, Ga, Nb, Zr, Ti, Si, and C are all added in high-purity elemental form with an elemental purity ≥99.95%.

[0102] A method for preparing a heavy rare-earth-free 54M NdFeB permanent magnet material includes the following steps:

[0103] S1. Batching and Vacuum Melting: Weigh each raw material according to the above-mentioned mass percentage formula, place the weighed raw materials into a vacuum induction melting furnace, and evacuate the furnace until the vacuum degree inside the furnace is ≤5×10. -3 Pa is filled with high-purity argon as a protective atmosphere, and smelting is carried out at 1520℃ for 18 minutes to completely melt the raw materials and obtain a uniform composition, thus obtaining an alloy melt.

[0104] S2. Rapid Solidification and Strip Spinning Preparation: The alloy melt obtained in step S1 is transferred to the heat preservation pot of the rapid solidification and strip spinning machine. The melt temperature is controlled at 1460℃ under a high-purity argon protective atmosphere (furnace vacuum degree ≤1×10⁻⁶). -2 The alloy melt is sprayed onto a high-speed rotating copper roller for spinning. The roller speed is controlled at 1.8 m / s to prepare a rapidly solidified alloy sheet with a thickness of 0.2~0.4 mm.

[0105] S3. Hydrogen Crushing Treatment: Place the rapidly solidified alloy sheet obtained in step S2 into a hydrogen crushing furnace, seal it, and then evacuate the furnace until the vacuum level is ≤1×10⁻⁶. -2 The furnace was charged with high-purity hydrogen gas (≥99.999%) until the internal hydrogen pressure reached 0.25 MPa. Hydrogen absorption was performed at room temperature for 2.5 hours to ensure complete hydrogenation and breakage of the alloy. Subsequently, the hydrogenated alloy underwent dehydrogenation treatment, and the furnace was evacuated to a vacuum level ≤1×10⁻⁶. -3 Pa, heat to 580℃, hold for 3.5h, and after dehydrogenation is completed, cool to room temperature and remove from the furnace to obtain hydrogen fragment powder. The particle size of the hydrogen fragment powder is controlled at 30~80 mesh.

[0106] S4. Ultrafine grinding by air jet milling: The hydrogen-rich powder obtained in step S3 is fed into an air jet mill. High-purity nitrogen gas with a purity ≥99.999% and an oxygen content ≤5ppm is used as the grinding medium. The grinding pressure is controlled at 0.9MPa and the classifier wheel speed is 4500rpm for ultrafine grinding to obtain a median particle size D. 50 The magnetic powder is 2.0~3.5μm in size; the entire process is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is strictly controlled to be ≤300ppm.

[0107] S5. Magnetic field orientation pressing and cold isostatic pressing: The magnetic powder obtained in step S4 is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The pressing pressure is controlled at 18MPa and the holding time is 10s to obtain an orientation compact. The compact is immediately vacuum sealed and then subjected to cold isostatic pressing. The cold isostatic pressing pressure is controlled at 220MPa and the holding time is 15s.

[0108] S6. Low-temperature sintering and two-stage aging treatment: The pressed billet obtained in step S5 is fed into a high-vacuum sintering furnace, and the entire process is carried out under a high-purity argon protective atmosphere, controlling the vacuum degree inside the furnace to ≤5×10⁻⁶. -3 Pa was subjected to low-temperature sintering and two-stage aging treatment in sequence: first, the temperature was raised to 1035℃ at a heating rate of 7℃ / min and held for 2.5h to complete sintering, followed by gas quenching with high-purity argon to room temperature; then, the temperature was raised to 860℃ at a heating rate of 9℃ / min and held for 1.5h before gas quenching to room temperature; finally, the temperature was raised to 500℃ at a heating rate of 9℃ / min and held for 2.5h before gas quenching to room temperature to obtain the sintered magnet.

[0109] S7. Post-processing: The sintered magnet obtained in step S6 is machined according to the application requirements to obtain the finished product of heavy rare earth 54M neodymium iron boron permanent magnet material.

[0110] Example 5

[0111] A heavy rare earth-free 54M neodymium iron boron permanent magnet material, comprising the following raw materials by mass percentage:

[0112] The alloy composition is as follows: PrNd 32%, B 1.08%, Co 2.0%, Cu 0.35%, Al 0.5%, Ga 0.2%, Nb 0.25%, Zr 0.2%, Ti 0.15%, Si 0.3%, C 0.05%, with the balance being Fe. The mass ratio of Pr to Nd in the PrNd alloy is 1:3, with an alloy purity ≥99.5% and Fe purity ≥99.9%. B is added in the form of a B-Fe alloy (B mass fraction in the B-Fe alloy is 20%). Co, Cu, Al, Ga, Nb, Zr, Ti, Si, and C are all added in high-purity elemental form with an elemental purity ≥99.95%.

[0113] A method for preparing a heavy rare-earth-free 54M NdFeB permanent magnet material includes the following steps:

[0114] S1. Batching and Vacuum Melting: Weigh each raw material according to the above mass percentage formula, place the weighed raw materials into a vacuum induction melting furnace, and evacuate the furnace until the vacuum degree inside the furnace is ≤5×10. -3 Pa is filled with high-purity argon as a protective atmosphere, and smelting is carried out at 1550℃ for 15 minutes to completely melt the raw materials and make the composition uniform, thus obtaining an alloy melt.

[0115] S2. Rapid Solidification and Strip Spinning Preparation: The alloy melt obtained in step S1 is transferred to the heat preservation pot of the rapid solidification and strip spinning machine. The melt temperature is controlled at 1480℃ under a high-purity argon protective atmosphere (furnace vacuum degree ≤ 1×10⁻⁶). -2 The alloy melt is sprayed onto a high-speed rotating copper roller for spinning. The roller speed is controlled at 2.0 m / s to prepare a rapidly solidified alloy sheet with a thickness of 0.2~0.4 mm.

[0116] S3. Hydrogen Crushing Treatment: Place the rapidly solidified alloy sheet obtained in step S2 into a hydrogen crushing furnace, seal it, and then evacuate the furnace until the vacuum level is ≤1×10⁻⁶. -2 The furnace was filled with high-purity hydrogen gas (≥99.999%) until the internal hydrogen pressure reached 0.3 MPa. Hydrogen absorption was performed at room temperature for 2 hours to ensure complete hydrogenation and breakage of the alloy. Subsequently, the hydrogenated alloy underwent dehydrogenation treatment, and the furnace was evacuated to a vacuum level ≤1×10⁻⁶. -3 Pa, heat to 600℃, hold for 3 hours, and after dehydrogenation is completed, cool to room temperature and remove from the furnace to obtain hydrogen fragment powder. The particle size of the hydrogen fragment powder is controlled at 30~80 mesh.

[0117] S4. Ultrafine grinding by air jet milling: The hydrogen-rich powder obtained in step S3 is fed into an air jet mill. High-purity nitrogen gas with a purity ≥99.999% and an oxygen content ≤5ppm is used as the grinding medium. The grinding pressure is controlled at 1.0MPa and the classifier wheel speed is 5000rpm for ultrafine grinding to obtain a median particle size D. 50The magnetic powder is 2.0~3.5μm in size; the entire process is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is strictly controlled to be ≤300ppm.

[0118] S5. Magnetic field orientation pressing and cold isostatic pressing: The magnetic powder obtained in step S4 is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The pressing pressure is controlled at 20MPa and the holding time is 5s to obtain an orientation compact. The compact is immediately vacuum sealed and then subjected to cold isostatic pressing. The cold isostatic pressing pressure is controlled at 250MPa and the holding time is 10s.

[0119] S6. Low-temperature sintering and two-stage aging treatment: The pressed billet obtained in step S5 is fed into a high-vacuum sintering furnace, and the entire process is carried out under a high-purity argon protective atmosphere, controlling the vacuum degree inside the furnace to ≤5×10⁻⁶. -3 Pa was subjected to low-temperature sintering and two-stage aging treatment in sequence: first, the temperature was raised to 1040℃ at a heating rate of 8℃ / min and held for 2 hours to complete sintering, and then high-purity argon gas was introduced for gas quenching to room temperature; then, the temperature was raised to 870℃ at a heating rate of 10℃ / min and held for 1 hour before being gas quenched to room temperature; finally, the temperature was raised to 510℃ at a heating rate of 10℃ / min and held for 2 hours before being gas quenched to room temperature to obtain the sintered magnet.

[0120] S7. Post-processing: The sintered magnet obtained in step S6 is machined according to the application requirements to obtain the finished product of heavy rare earth 54M neodymium iron boron permanent magnet material.

[0121] Comparative Example 1 (Core components with missing grains and refined structure)

[0122] Formula adjustment: Remove Nb, Zr and Ti from Example 3, and keep the remaining components and contents the same as in Example 3, with the remainder being Fe.

[0123] Preparation process: exactly the same as in Example 3.

[0124] Comparative Example 2 (lacking grain boundary regulation core components)

[0125] Formula adjustment: Remove Cu, Al and Ga from Example 3, and keep the remaining components and contents the same as in Example 3, with the remainder being Fe.

[0126] Preparation process: exactly the same as in Example 3.

[0127] Comparative Example 3 (lacking the core component for high-temperature stability)

[0128] Formula adjustment: Remove Co from Example 3, and keep the remaining components and contents the same as in Example 3, with the remainder being Fe.

[0129] Preparation process: exactly the same as in Example 3.

[0130] Comparative Example 4 (Core sintering process parameters exceed the limits of this invention)

[0131] Formula: exactly the same as in Example 3.

[0132] Process adjustments: The sintering temperature was set to 1070℃ (exceeding the temperature range of 1020~1040℃ limited by this invention), the holding time was set to 3h, and the rest of the preparation process was the same as in Example 3.

[0133] Comparative Example 5 (Deficiency of Time-Aging Process and Failure of Low-Oxygen Control Throughout the Process)

[0134] Formula: exactly the same as in Example 3.

[0135] Process adjustments: The two-stage aging process in step S6 is cancelled and replaced with a single-stage aging process at 500℃ for 5 hours. At the same time, the low oxygen control throughout the process is abandoned, and the inert gas protection is cancelled in the magnetic powder preparation and pressing molding process. The rest of the preparation process is the same as in Example 3.

[0136] To systematically verify the performance compliance of the heavy rare earth-free 54M NdFeB permanent magnet material and the effectiveness of its core formulation and process design, performance testing was conducted on all magnet samples prepared in Examples 1-5 and Comparative Examples 1-5. All samples were uniformly processed into standard Φ10mm×10mm test specimens. Three samples were prepared in parallel for each group, and the average value was taken to ensure the accuracy and repeatability of the test data. The specific testing content, methods, and results are as follows:

[0137] I. Test Items, Implementation Standards, and Test Methods

[0138] 1. Core Magnetic Performance Testing: The test items include remanence Br, intrinsic coercivity Hcj, maximum energy product (BH)max, and squareness Hk / Hcj of the demagnetization curve. The tests are conducted in accordance with GB / T 3217-2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials" and GB / T13560-2017 "Sintered NdFeB Permanent Magnet Materials". A high-precision permanent magnet material BH tester is used for closed-loop testing at room temperature of 25℃. The squareness is obtained by reading the magnetic field strength Hk corresponding to the magnetic induction intensity dropping to 0.9Br from the demagnetization curve and calculating the ratio of Hk to intrinsic coercivity Hcj.

[0139] 2. High-Temperature Stability Testing: The test items include Curie temperature Tc and coercivity retention rate at 120℃, performed according to GB / T 3217-2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials". The Curie temperature was tested using differential scanning calorimetry (DSC) at a heating rate of 10℃ / min, with a test range from room temperature to 400℃. For coercivity retention, the intrinsic coercivity Hcj at room temperature (25℃) was tested first. Then, the sample was placed in a high-low temperature chamber and heated to 120℃, held for 30 minutes until the temperature was completely stable, and then the intrinsic coercivity Hcj at 120℃ was tested. The calculation formula is: Coercivity retention rate = (Intrinsic coercivity at 120℃ / Intrinsic coercivity at 25℃) × 100%.

[0140] 3. Physical Performance Testing: The tests include the oxygen content and density of the magnet. The oxygen content test follows GB / T12690.4-2021 "Chemical Analysis Methods for Non-Rare Earth Impurities in Rare Earth Metals and Their Oxides Part 4: Determination of Oxygen and Nitrogen Content - Pulse-Infrared Absorption Method and Pulse-Thermal Conductivity Method," using a pulse infrared oxygen-nitrogen analyzer. A sample cut from the center is used for testing. The density test follows GB / T 3850-2015 "Dense Sintered Metal Materials and Hard Alloys - Determination of Density," using the Archimedes water displacement method. The actual density of the sample is tested in a deionized water environment at 25℃, and the density is calculated based on the material's theoretical density.

[0141] 4. Microstructure Detection: The test items include the average grain size of the main phase and the average thickness of the grain boundary phase. The average grain size of the main phase was tested according to GB / T 6394-2017 "Method for Determination of Average Grain Size of Metals". The polished and etched cross section of the magnet was observed using a field emission scanning electron microscope. Five non-overlapping fields of view were selected, and the average grain size of the main phase was statistically calculated using the linear intercept method. The average thickness of the grain boundary phase was obtained by observing the ultrathin section of the magnet using a high-resolution transmission electron microscope. Ten different grain boundary locations were selected, and the average thickness of the grain boundary phase was statistically calculated.

[0142] II. Test Results

[0143] The specific test results are shown in Table 1 and Table 2, respectively.

[0144]

[0145]

[0146] III. Test Result Analysis

[0147] 1. Compliance of core magnetic properties

[0148] All samples from Examples 1-5 of this invention consistently met the core performance requirements of the 54M grade. Specifically, the maximum energy product (BH)max was consistently between 54.16 and 54.95 MGOe, the intrinsic coercivity Hcj was consistently between 14.23 and 15.24 kOe, the remanence Br was consistently between 14.53 and 14.82 kGs, and the squareness of the demagnetization curve Hk / Hcj > 93%. Under conditions where no heavy rare earth elements such as Dy and Tb were added, a synergistic improvement in high energy product and high coercivity was achieved, along with excellent dynamic demagnetization resistance. These performance indicators reached the advanced level in China. In contrast, all comparative samples failed to consistently meet the performance thresholds of the 54M grade. The highest maximum energy product was only 52.31 MGOe, the highest intrinsic coercivity was only 13.85 kOe, and the highest squareness of the demagnetization curve was only 88.7%, with all core magnetic properties showing significant attenuation to varying degrees.

[0149] 2. Analysis of the role of key components

[0150] Comparative Example 1 lacks the core grain-refining components Nb, Zr, and Ti of this invention, and cannot form nano-precipitates at the grain boundaries to achieve the pinning effect. The main phase grain size increases to 5.98 μm, and the intrinsic coercivity eventually decreases to 10.72 kOe. The squareness of the demagnetization curve is only 85.3%, which completely fails to meet the performance requirements of grade 54M. This fully verifies the core role of this group of elements in ultrafine grain control and coercivity enhancement.

[0151] Comparative Example 2 lacks the core grain boundary regulation components Cu, Al, and Ga of this invention, which cannot optimize the wettability of the rare earth-rich grain boundary phase. The average thickness of the grain boundary increases to 7.83 nm, and it is distributed in an island-like discontinuous manner. The exchange coupling effect between grains is significant, and the remanence and coercivity are simultaneously and significantly reduced. This fully verifies the key role of this group of elements in the construction of ultrathin continuous grain boundaries and the synergistic improvement of magnetic properties.

[0152] Comparative Example 3 lacks the core high-temperature stability component Co of this invention, resulting in a Curie temperature of 308.6℃ for the main phase and a coercivity retention rate of only 55.74% at 120℃. The magnetic properties are severely degraded at high temperatures, and the intrinsic coercivity at room temperature is only 13.85 kOe, which cannot meet the high-temperature operating requirements of high-end application scenarios. This fully verifies the core role of Co in improving the high-temperature performance and performance margin of magnets.

[0153] Comparative Example 4 uses a high-temperature sintering process that exceeds the scope of this invention. The main phase grains grow abnormally to 7.53 μm, the grain boundary structure is completely destroyed, and the magnetic properties are severely degraded. This fully verifies the necessity of the low-temperature short-time sintering process of this invention for grain refinement and magnetic property protection.

[0154] Comparative Example 5 lacks the dual-stage aging process of the present invention, and the low-oxygen control throughout the process fails. The oxygen content of the magnet is as high as 750 ppm, the density is only 98.10%, the main phase grains show local oxidation, the grain boundary phase distribution is disordered, and the magnetic properties eventually drop sharply, failing to meet the usage requirements. This fully verifies the core value of the dual-stage aging process and the low-oxygen control throughout the process of the present invention.

[0155] 3. High-temperature stability evaluation

[0156] The Curie temperatures of the samples in this invention all reached above 332℃, and the coercivity retention rate at 120℃ was ≥71%, with a maximum of 79.91%, far exceeding the national standard operating temperature requirements. This demonstrates stable compatibility with high-temperature operating scenarios at 120℃, solving the problem of insufficient high-temperature stability in traditional non-heavy rare-earth NdFeB alloys. In contrast, the coercivity retention rates of all comparative samples at 120℃ ranged from a maximum of 62.28% to a minimum of 52.10%, making it difficult to stably adapt to operating scenarios above 100℃. Their high-temperature performance is significantly inferior to that of this invention.

[0157] 4. Microstructure characterization

[0158] The main phase grain size of the samples in this embodiment of the invention is stably controlled at 2.14~2.97μm. The uniform ultrafine grain structure provides the core structural basis for the high coercivity of the magnet. The grain boundary thickness is controlled at 1.24~1.82nm, exhibiting a continuous and uniform ultrathin state, completely wetting the main phase grains and effectively eliminating the exchange coupling effect between grains. While significantly improving the coercivity, it minimizes the loss of relative remanence at the grain boundaries. At the same time, the oxygen content of the magnets is ≤440ppm and the density is ≥99.5%, effectively avoiding the attenuation of magnetic properties caused by oxide impurities, ensuring the batch stability of magnetic properties, and fully verifying the scientificity and rationality of the synergistic control of the formulation and process of this invention.

[0159] The above content should not be construed as limiting the specific implementation of this invention to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of this invention, and all such deductions or substitutions should be considered as falling within the patent protection scope defined by the submitted claims.

Claims

1. A heavy rare earth-free 54M NdFeB permanent magnet material, characterized in that, The composition, by mass percentage, includes the following raw materials: PrNd 28~32%, B 0.98~1.08%, Co 1.0~2.0%, Cu 0.15~0.35%, Al 0.2~0.5%, Ga 0.08~0.2%, Nb 0.1~0.25%, Zr 0.08~0.2%, Ti 0.05~0.15%, Si 0.1~0.3%, C 0.02~0.05%, with the balance being Fe.

2. The heavy rare earth-free 54M NdFeB permanent magnet material according to claim 1, characterized in that, The mass ratio of Pr to Nd in the PrNd is 1:

3.

3. The heavy rare earth-free 54M NdFeB permanent magnet material according to claim 1, characterized in that, The purity of PrNd is ≥99.5%, and the purity of Fe is ≥99.9%; B is added in the form of ferroborone alloy, and the mass fraction of B in the ferroborone alloy is 20%; Co, Cu, Al, Ga, Nb, Zr, Ti, Si and C are all added in the form of high-purity elements, and the purity of the elements is ≥99.95%.

4. A method for preparing a heavy rare earth-free 54M NdFeB permanent magnet material according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Batching and Vacuum Melting: Weigh the raw materials according to the formula, place them in a vacuum induction melting furnace, and evacuate to a vacuum level of ≤5×10⁻⁶. -3 Pa, filled with high-purity argon gas for protection, melted and held at 1450~1550℃ for 15~30min to obtain a uniform alloy melt; S2. Preparation of rapidly solidified alloy sheets: The alloy melt is transferred to the heat preservation bag of the rapidly solidified alloy sheet casting machine, and the melt temperature is controlled at 1400~1480℃. Under the protection of high-purity argon gas, the alloy melt is sprayed onto a high-speed rotating copper roller for casting. The roller speed is 1.2~2.0m / s, and rapidly solidified alloy sheets are prepared. S3. Hydrogen-crushing treatment: Place the rapidly solidified alloy sheet into a hydrogen-crushing furnace, seal it, and then evacuate it to ≤1×10⁻⁶. -2 Pa, purge with high-purity hydrogen until the hydrogen pressure inside the furnace is 0.1~0.3 MPa, and absorb hydrogen at room temperature for 2~4 hours; then evacuate to ≤1×10 -3 Pa, heat to 500~600℃ and hold for 3~5h to remove hydrogen, and after cooling, obtain 30~80 mesh hydrogen fragment powder; S4. Ultrafine grinding by air jet milling: Hydrogen-crushed powder is fed into an air jet mill, using high-purity nitrogen as the grinding medium. The grinding pressure is controlled at 0.6~1.0 MPa and the classifier speed at 3500~5000 rpm to obtain a median particle size D. 50 Magnetic powder with a particle size of 2.0~3.5μm; S5. Magnetic field orientation pressing and cold isostatic pressing: Magnetic powder is loaded into a non-magnetic mold and pressed in a parallel magnetic field with an orientation magnetic field strength ≥1.8T. The forming pressure is controlled at 10~20MPa and the holding time is 5~20s to obtain an orientation compact; after vacuum sealing, the compact is cold isostatically pressed at a pressure of 150~250MPa for 10~30s. S6. Low-temperature sintering and two-stage aging treatment: The compact is fed into a high-vacuum sintering furnace, with high-purity argon gas protection throughout the process, and the vacuum degree inside the furnace is ≤5×10⁻⁶. -3 Pa, first heat to 1020~1040℃ and hold for 2~4h to complete sintering, then quench with argon gas to room temperature; then heat to 830~870℃ and hold for 1~3h, then quench with argon gas to room temperature; finally heat to 470~510℃ and hold for 2~4h, then quench with argon gas to room temperature to obtain sintered magnet. S7. Post-processing: The sintered magnets are mechanically processed as required to obtain the finished product of heavy rare earth-free 54M neodymium iron boron permanent magnet material.

5. The preparation method of the heavy rare earth-free 54M NdFeB permanent magnet material according to claim 4, characterized in that, In step S2, under the protective atmosphere of high-purity argon, the vacuum level inside the furnace is controlled to be ≤1×10⁻⁶. -2 Pa.

6. The method for preparing the heavy rare earth-free 54M NdFeB permanent magnet material according to claim 4, characterized in that, In step S2, the thickness of the rapidly solidified alloy sheet is 0.2~0.4 mm, and the mass percentage of the α-Fe phase is ≤5%.

7. The method for preparing the heavy rare earth-free 54M NdFeB permanent magnet material according to claim 4, characterized in that, In step S4, the high-purity nitrogen gas has a purity of ≥99.999% and an oxygen content of ≤5ppm.

8. The method for preparing the heavy rare earth-free 54M NdFeB permanent magnet material according to claim 4, characterized in that, In step S4, the ultrafine powdering process of the air jet mill is carried out under an inert atmosphere, and the oxygen content of the magnetic powder is controlled to be ≤300ppm.

9. The preparation method of the heavy rare earth-free 54M NdFeB permanent magnet material according to claim 4, characterized in that, In step S6, the temperature is first increased to 1020-1040℃ at a rate of 3-8℃ / min; then increased to 830-870℃ at a rate of 5-10℃ / min; and finally increased to 470-510℃ at a rate of 5-10℃ / min.

10. A heavy rare earth-free 54M NdFeB permanent magnet material prepared by the method according to any one of claims 4 to 9, characterized in that, The permanent magnet material has a remanence Br≥14.5kGs, intrinsic coercivity Hcj≥14kOe, maximum energy product (BH)max≥54MGOe, and coercivity retention rate ≥70% at 120℃.

Citation Information

Patent Citations

  • Neodymium-iron-boron magnet material and preparation method and application thereof

    CN120319600A

  • Neodymium-iron-boron magnet without heavy rare earth addition and preparation method of neodymium-iron-boron magnet

    CN121191875A

  • Heavy-rare-earth-free high-performance sintered neodymium-iron-boron magnet and preparation method thereof

    CN121331582A

  • Neodymium-iron-boron magnet without heavy rare earth and preparation method thereof

    CN121565610A